Towards more rigorous assessment of biodiversity - Vanclay, J.K. (1998)
Biodiversity is often ill-defined and subjectively surveyed, resulting in inefficient and ambiguos estimates. Strengths and deficiencies of prevailing survey techniques are appraised through a review of selected literature. Analogies with forest inventory are used to suggest options for more efficient and rigorous biodiversity assessment. Techniques such as variable-probability and model-based sampling, especially when used in conjuction with generalised linear modelling, offer efficient alternatives to more traditional assessment based on quadrats and nested plots. Bayesian methods offer scope to combine expert and local knowledge with formal samples, and warrant further investigation. Suggestion for further research are given.